2016
DOI: 10.1590/0101-60830000000101
|View full text |Cite
|
Sign up to set email alerts
|

Simple markers for subclinical inflammation in the different phases of bipolar affective disorder

Abstract: Background: Recently, a growing number of publications have suggested that the immune-inflammatory system may be involved in the etiology of bipolar disorder (BD). Objective: The aim of this study was to investigate neutrophil-lymphocyte ratio (NLR), platelet-lymphocyte ratio (PLR), and red cell distribution width (RDW) in the three different phases of BD patients compared to each other and controls. Methods: One hundred eighty-seven bipolar patients (78 euthymic, 53 manic/hypomanic and 56 depressed), and 62 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 31 publications
(41 reference statements)
0
11
0
Order By: Relevance
“…In a study with a similar method by Yıldız et al, PLR was found not to be different in all patient groups compared to the control group in consistent with our results. It has also been reported that NLR was higher only in patients with the euthymic and manic phase and there was no difference between the depressive group and control group in terms of NLR [33]. Including only drug-free patients for at least 1 month in the current study may lead to different results in the patients with depressive phase in terms of NLR.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…In a study with a similar method by Yıldız et al, PLR was found not to be different in all patient groups compared to the control group in consistent with our results. It has also been reported that NLR was higher only in patients with the euthymic and manic phase and there was no difference between the depressive group and control group in terms of NLR [33]. Including only drug-free patients for at least 1 month in the current study may lead to different results in the patients with depressive phase in terms of NLR.…”
Section: Discussionmentioning
confidence: 70%
“…Studies in which inflammatory mechanisms play a role in the aetiology of BD are becoming increasingly important. According to our knowledge, three studies have investigated the association between NLR or PLR and BD to date [31][32][33]. However, the results of these studies vary according to different episodes of BD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers have investigated the PLT levels in psychiatric disorders. In many studies, the differences between BD and UD patients and control groups were not statistically significant [5,8,20,22,23]. Kalelioğlu et al found higher PLT counts in the control group than among BD patients [21].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, several hemogram parameters have been investigated to evaluate the inflammatory states in both organic (27,28) and psychiatric disorders in recent publications. There are several studies investigating the hemogram parameters of adult patients with a major depressive disorder (29,30), bipolar disorder (31) and schizophrenia (32). Basic points in the investigation of these parameters are based on the ease of use and economical in daily practice.…”
mentioning
confidence: 99%